Some Suggestions as to Our Mural Antiquities (Proceedings of the Society of Antiquaries of Scotland, 1877)
This article discusses how church monuments and sculptured stones are often under-documented in Scotland because they are not discovered by or brought to the attention of experts. To encourage Fellows of the Society to study these monuments, he presents a series of sketches of sculptured stones and describes where they were found.